Design of Four Phase Switched Reluctance Motor Type 8/6 for Optimized Torque (Damascus University Journal for engineering sciences, 2022)
The switched reluctance motor (SRM) is widely used over other motors for variable speed drive application and several industrial applications because of low cost and simple structure.This paper presents effect of variation for stator/ rotor angle on four phase switched reluctance motor type 8/6 torque using finite element analysis and ansys Maxwell 3D.This study describes a procedure for optimizing the stator and rotor pole of a double saliency four phase switched reluctance motor type 8/6 to maximize the electromagnetic torque.This research is very essential to study all cases of design four phase switched reluctance motor type 8/6 and its torque value.
Keywords: Switched Reluctance Motor; Finite element analysis; Anysis; Optimizing Torque